1998
DOI: 10.1007/s002130050613
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines enhance the consumption and palatability of alcohol in the rat

Abstract: This study examined the effect of the benzodiazepine, midazolam, on the consumption and palatability of 6% ethanol in male Wistar rats. In the first experiment, it was found that midazolam (5 mg/kg) increased home cage ethanol drinking 0-2 h after administration. Another intake experiment, in which ethanol was infused directly into the oral cavity through an indwelling catheter, also showed that midazolam (10 mg/kg) stimulated alcohol ingestion. The affective response to intraoral infusions of ethanol (1 ml du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
2
16
2
Order By: Relevance
“…Consistent with this hypothesis is the observation that classical anxiolytics (e.g., benzodiazepines) have the ability to increase non-dependent ethanol self-administration (Soderpalm and Hansen, 1998) and the same dose (0.25 mg/kg) of prazosin was able to attenuate the anxiogenic effects of nicotine administration in the elevated plus-maze (Zarrindast et al, 2000). An alternative explanation for the selective increases in self-administration observed in nondependent animals is that the low dose of prazosin is by some method increasing stress and thereby causing increased self-administration.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with this hypothesis is the observation that classical anxiolytics (e.g., benzodiazepines) have the ability to increase non-dependent ethanol self-administration (Soderpalm and Hansen, 1998) and the same dose (0.25 mg/kg) of prazosin was able to attenuate the anxiogenic effects of nicotine administration in the elevated plus-maze (Zarrindast et al, 2000). An alternative explanation for the selective increases in self-administration observed in nondependent animals is that the low dose of prazosin is by some method increasing stress and thereby causing increased self-administration.…”
Section: Discussionmentioning
confidence: 73%
“…The results indicated that a priming dose of the GABAergic neurosteroid ALLO or exposure to a CS previously paired with reinforcer delivery reinstated ethanol-seeking and sucrose-seeking behavior in mice. The majority of evidence supporting GABAergic involvement in the regulatory processes governing ethanol intake (Rassnick et al, 1993; Hodge et al, 1995, 1996; Hyytiä and Koob, 1995; Petry, 1997; Shelton and Balster, 1997; Janak et al, 1998; June et al, 1998a, 1998b; Nowak et al, 1998; Soderpalm and Hansen, 1998; Samson and Chappell, 2001; Sinnott et al, 2002b; Janak and Gill, 2003; Ford et al, 2005a, 2005b, 2007b; Krystal et al, 2006) indicate a relatively selective effect of GABA A receptor ligands on ethanol consumption, although benzodiazepines also have been reported to alter saccharin and food consumption in rats (e.g., Wegelius et al, 1994; Shelton and Balster, 1997). Collectively, the present findings in mice support a role of GABAergic neurosteroids such as ALLO in general motivation.…”
Section: Discussionmentioning
confidence: 99%
“…They may, therefore, be subject to abusive use or reinforce drug-seeking behaviors in alcoholics (Soderpalm and Hansen, 1998;Schmitt et al, 2002;Isbister et al, 2004;O'Brien C, 2005). Our data indicate that NPS alleviates anxiety and depression at doses that do not elicit CPP, but nevertheless actually reduce EtOH consumption.…”
Section: Discussionmentioning
confidence: 99%
“…BZDs, in turn, are themselves habit-forming. Importantly, BZDs have also been shown to increase the palatability of EtOH and increase alcohol consumption (Soderpalm and Hansen, 1998). Thus, there is a significant need for novel targets and treatments for anxiety disorders, especially for anxiety that is co-morbid with alcoholism.…”
Section: Introductionmentioning
confidence: 99%